Twórczość artystyczna jako sposób urzeczywistniania paradygmatu emancypacyjnego - Pawlik, Sabina (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
The article relates to artistic creation of intellectually disabled people as an example of possible means of their emancipation. In this paper I claim that artistic creation of intellectually disabled people may constitute a tool of self-expression, and as a result be a way to realize the emancipatory paradigm in special education. I have illustrated my hypothesis with some poetry written by two women affected by Down syndrome whose creation is a conscious act of formulating an autonomous artistic message.